Amino Acid Changes in the Influenza A Virus PA Protein That Attenuate Avian H5N1 Viruses in Mammals - Fan, Shufang (J Virol, 2014)
The influenza viral polymerase complex affects host tropism and pathogenicity. In particular, several amino acids in the PB2 polymerase subunit are essential for the efficient replication of avian influenza viruses in mammals. The PA polymerase subunit also contributes to host range and pathogenicity. Here, we report that the PA proteins of several highly pathogenic avian H5N1 viruses have attenuating properties in mammalian cells and that the attenuating phenotype is conferred by strain-specific amino acid changes. Specifically, lysine at position 185 of A/duck/Vietnam/TY165/2010 (TY165; H5N1) PA induced strongly attenuating effects in vitro and in vivo. More importantly, the introduction of the arginine residue commonly found at this position in PA significantly increased the viral polymerase activity of TY165 in mammalian cells and its virulence and pathogenicity in mice. These findings demonstrate that the PA protein plays an important role in influenza virulence and pathogenicity. IMPORTANCE Highly pathogenic influenza viruses of the H5N1 subtype cause severe respiratory infections in humans, which have resulted in death in nearly two-thirds of the patients with laboratory-confirmed cases. We found that the viral PA polymerase subunit of several H5N1 viruses possesses amino acid changes that attenuate virus replication in mammalian cells (yet the H5N1 viruses possessing these mutations are highly pathogenic in mice). Specifically, we found that an arginine-to-lysine substitution at position 185 of an H5N1 virus PA protein significantly affected that virus's virulence and pathogenicity in mice. The PA protein thus plays a role in the pathogenicity of highly pathogenic H5N1 influenza viruses.